Takhrij sebagai Metode Penelusuran Kualitas Hadits Ahad - Bahrudin Bahrudin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2009)
Otenticity and originality a religion is a lot of prescribed by how far a grasp and doing of religion by someone has suitability with teachings subject sources, namely main clarifying source in the presence that religion is alone. This condition of signs that divides person that will grasp pattern and pengamalan of religion that really obviously it gains control many that source knowledge discipline. E.g. takhrijul hadits, this discipline gets to help someone in see position a hadits what reasonably hadits that fulfillment of standard or not.